Current Status of Autophagy Enhancers in Metabolic Disorders and Other Diseases - Park, Kihyoun; Lee, Myung-Shik (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is pivotal in the maintenance of organelle function and intracellular nutrient balance. Besides the role of autophagy in the homeostasis and physiology of the individual tissues and whole organism in vivo, dysregulated autophagy has been incriminated in the pathogenesis of a variety of diseases including metabolic diseases, neurodegenerative diseases, cardiovascular diseases, inflammatory or immunological disorders, cancer and aging. Search for autophagy modulators has been widely conducted to amend dysregulation of autophagy or pharmacologically modulate autophagy in those diseases. Current data support the view that autophagy modulation could be a new modality for treatment of metabolic syndrome associated with lipid overload, human-type diabetes characterized by deposition of islet amyloid or other diseases including neurodegenerative diseases, infection and cardiovascular diseases. While clinically available bona fide autophagy modulators have not been developed yet, it is expected that on-going investigation will lead to the development of authentic autophagy modulators that can be safely administered to patients in the near future and will open a new horizon for treatment of incurable or difficult diseases.